From pensions to pupils? Schooling, resource constraints and old age pensions in Ireland 1901-11 - Tiarnán Heaney (Queen's University Centre for Economic History (QUCEH), 2024)
A large literature argues that resource constraints inhibit human capital accumulation. We test this hypothesis using the introduction of the Old Age Pension in Ireland in 1908, evaluating its spillover on school enrolments within multigenerational households. Exploiting the OAP's age-based and means-test criteria, we identify the causal effect of the cash transfer on enrolments for children aged 14 to 16 using data from the 1901 and 1911 Censuses of Ireland. The OAP increased the school enrolments of the poorest children by 8 per cent, while no effect is detected for wealthier households. This suggests that when poverty constrains schooling, unconditional cash transfers amplify a household's demand for education by reducing the opportunity costs of schooling.
Keywords: D31; H55; I25; J18; J24; N33; 330; schooling; poverty; old age pension; cash transfer; human capital; economic history of Ireland